2008
DOI: 10.1179/136404608x362016
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue properties of Al–Si casting alloy with cold sprayed Al/SiC coating

Abstract: The fatigue properties of Al-Si alloy cold sprayed Al and Al-SiC composite coatings have been studied. The specimens coated with composites reinforced with a large volume (25%) of fine SiC particles exhibited improved adhesion strength at the interface due to crater formation, and cyclic fatigue lives at room temperature more than three times those of uncoated specimens. In high temperature low cycle fatigue tests at 250uC, the pure Al coatings showed longer fatigue lives than the Al-SiC composite coatings, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
(3 reference statements)
0
13
0
Order By: Relevance
“…Mg and Al alloys) due to the presence of compressive residual stresses in the coating, as it reduces the effective applied stress and retards crack initiation and propagation [65,67,68]. The high cycle fatigue performance of Al-Si alloy was reported to be increased by >200% after applying Al-SiC composite coating by CS [69]. Moreover, it is hypothesized that compressive residual stresses may also contribute towards the increased coating-substrate adhesion strength [70].…”
Section: Influence On the Mechanical Propertiesmentioning
confidence: 99%
“…Mg and Al alloys) due to the presence of compressive residual stresses in the coating, as it reduces the effective applied stress and retards crack initiation and propagation [65,67,68]. The high cycle fatigue performance of Al-Si alloy was reported to be increased by >200% after applying Al-SiC composite coating by CS [69]. Moreover, it is hypothesized that compressive residual stresses may also contribute towards the increased coating-substrate adhesion strength [70].…”
Section: Influence On the Mechanical Propertiesmentioning
confidence: 99%
“…This case has been found on thermal spray coatings and can be explained by the solidification and consequent cooling to room temperature of the successively deposited layers [1][2][3][4]. On the other hand, compressive residual stress is beneficial for the coatings and can improve the fatigue life [1,[5][6][7][8][9]. Many studies have reported that cold spray coatings exhibit a beneficial compressive residual stress [3,6,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 86%
“…Compared to other methods such as physical and chemical vapour deposition, radio frequency Magnetron sputtering is an attractive approach to produce a SiC coating on various substrates with evidence of improving the surface properties [4][5][6][7][8][9][10]. Axelevitch et al investigated the feasibility tests of SiC thin films by sputtering and found that the obtained films were transparent and behaved as dielectric in the Al-Si x -Al and Al-Si x C y -Si structure [11].…”
Section: Introductionmentioning
confidence: 99%